PERAN GURU DALAM MENUMBUHKAN KEAKTIFAN PESERTA DIDIK MELALUI WHATSAPP GROUP PADA MASA PANDEMI DI SEKOLAH DASAR NEGERI 4 KUBU BANGLI (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Abstract: This study aims to provide an overview of the teacher's role in growing student activity through whatsapp groups during the pandemic at SD Negeri 4 Kubu Bangli. The type used in this research is qualitative research using a qualitative descriptive approach. The research was conducted at SD Negeri 4 Kubu, using primary and secondary data sources. The subjects in the study were school principals, fourth and sixth grade teachers and fourth and sixth grade students and used data collection techniques in which researchers used observation, interviews, library research, and documentation studies. The data that has been collected was analyzed using qualitative descriptive techniques. Based on the results of research and data analysis, it shows that (1) the contribution of teachers in growing the activeness of students through WhatsApp groups during the pandemic has been very good as a learning medium. (2) the obstacles faced by the teacher in growing the activeness of students through whatsap groups include factors of facilities and infrastructure, teachers, and students. (3) the efforts made by the teacher in overcoming obstacles to foster student activity through whatsapp groups during the pandemic, including using innovative and creative methods, motivating students, and supporting facilities and infrastructure in the learning process.